Efficacy of selected volatile compounds for organic vine mealybug control - Peschiutta, María Laura (2019)
Planococcus ficus (Signoret) (Hemiptera: Pseudo-coccidae) constitutes a high impact pest in vineyards. Synthetic insecticides are inefficient to control the mealybug population and they affect human health and the environment. The insecticidal properties of eight volatile compounds against vine mealybugs and their grapevine leaf phytotoxicity in laboratory conditions were evaluated. 2-decanone, 3-decanone, α-methyl cinnamaldehyde and cinnamaldehyde produced a higher percentage of mealybug mortality in relation to control at a fumigant dose of 300 μL·L-1 air. The 3-octanone, cinnamyl chloride, 1-octen-3-ol and 3-octanol were not effective against P. ficus. Cinnamaldehyde and α-methyl cinnamaldehyde produced a low acetylcholinesterase inhibition (IC50= 2.67 μL·L-1 and 9.10 μL·L-1, respectively), whereas 2-decanone and 3-decanone did not cause enzyme inhibition. Cinnamaldehyde was not phytotoxic for grapevine leaves; therefore, this compound was selected for a contact application to improve its effectiveness, resulting in a LC50 of 394.36 μL·L-1 solution. The results demonstrated the potential of cinnamaldehyde to be developed as a non-phytotoxic natural insecticide for the control of vine mealybugs in vineyards.